Empirical Analysis of Cost Efficiency and Loan Loss Provision of African Commercial Banks: Comparison with UK Banks - Olujobi, Oluwadamisi (2019)
This research empirically compared Loan Loss Provisioning (LLP) behaviour of African banks (Nigeria and South Africa) with UK banks in relation to three hypothesis- income smoothing, capital management and business cycle. In the meantime, it also examined if cost-efficiency influences loan loss provisioning behaviour. Using a panel data from 2013- 2017, the Stochastic Frontier Analysis and Generalized Method of Moments were used to estimate efficiency scores and factors affecting LLP behaviour respectively. Results reported that all banks are cost-efficient and cost efficiency influences LLP behaviour. Results provided evidence of income smoothing for both African and UK banks, then the business cycle for African banks. However, there was no evidence of capital management for both African and UK banks likewise there was no evidence of business cycle hypothesis for UK banks. Furthermore, results showed that lagged loss provision and credit risk affects LLP for both banks, including liquidity risk and size for UK banks. Interestingly, negative credit risk regressions were robust for both Nigeria and South Africa. In all, income-smoothing hypothesis, business cycle and credit risk show that there is a difference between LLP behaviour for African banks and the UK. Provisioning is backward-looking for African banks and forward-looking for UK banks.